CD226 identifies functional CD8+T cells in the tumor microenvironment and predicts a better outcome for human gastric cancer - Huang, Hao; Huang, Ziyi; Ge, Junwei; Yang, Jiayi; Chen, Junjun; Xu, Bin; Wu, Shaoxian; Zheng, Xiao; Chen, Lujun; Zhang, Xueguang; Jiang, Jingting (Frontiers in Immunology, 2023)
It is well-known that CD226 serves as a critical activating receptor on various immune cells, such as lymphocytes and monocytes, and it is suggested to promote anti-tumor immunity in the tumor microenvironment (TME). Herein, we showed a crucial regulatory role of CD226 in CD8+T cell-mediated anti-tumor response in TME of human gastric cancer (GC). Specifically, the increased CD226 expression in cancer tissues was significantly associated with better clinical outcomes in GC patients. Moreover, the increased infiltrating CD226+CD8+T cells and the increased ratio of infiltrating CD226+CD8+T cells in CD8+T subpopulation within cancer tissues could also be valuable prognostic predictors for GC patients. Mechanically, the assay for transposase-accessible chromatin using sequencing (ATAC-seq) analysis revealed that the chromatin accessibility of CD226 in CD4+ and CD8+TILs was significantly higher than that in CD8+T cells in normal tissues. Further analysis showed that CD8+TILs highly expressed immune checkpoint molecules, such as TIGIT, LAG3, and HAVCR2, which means CD8+TILs are more exhausted. In addition, our multi-color immunohistochemical staining (mIHC) revealed that GC patients with higher frequency of IFN-γ+CD226+CD8+TILs showed poorer prognosis. Combined with the single-cell transcriptome sequencing (scRNA-seq) data analysis, we found that the expressions of IFN-γ and TIGIT in CD8+TILs were significantly and positively correlated. The expression of TIGIT in IFN-γ+CD226+CD8+TILs was high, while that in IFN-γ-CD226+CD8+TILs was significantly lower. The correlation analysis showed that the expression of CD226 was positively correlated with the score of effector T cells but negatively correlated with that of immunosuppressive factors, such as Tregs and tumor-associated macrophages (TAMs). Collectively, we showed that the intensity of CD226+CD8+TILs was an excellent prognostic predictor for GC patients. Our findings provided insights into the interaction pattern between co-stimulatory receptor CD226 and tumor cells as well as the infiltrating immune cells in the TME in GC.